Resveratrol and para-coumarate serve as ring precursors for coenzyme Q biosynthesis[S] - Xie, Letian X.; Williams, Kevin J.; He, Cuiwen H.; Weng, Emily; Khong, San; Rose, Tristan E.; Kwon, Ohyun; Bensinger, Steven J.; Marbois, Beth N.; Clarke, Catherine F. (Journal of lipid research, 2015)
Coenzyme Q (Q or ubiquinone) is a redox-active polyisoprenylated benzoquinone lipid essential for electron and proton transport in the mitochondrial respiratory chain. The aromatic ring 4-hydroxybenzoic acid (4HB) is commonly depicted as the sole aromatic ring precursor in Q biosynthesis despite the recent finding that para-aminobenzoic acid (pABA) also serves as a ring precursor in Saccharomyces cerevisiae Q biosynthesis. In this study, we employed aromatic 13C6-ring-labeled compounds including 13C6-4HB, 13C6-pABA, 13C6-resveratrol, and 13C6-coumarate to investigate the role of these small molecules as aromatic ring precursors in Q biosynthesis in Escherichia coli, S. cerevisiae, and human and mouse cells. In contrast to S. cerevisiae, neither E. coli nor the mammalian cells tested were able to form 13C6-Q when cultured in the presence of 13C6-pABA. However, E. coli cells treated with 13C6-pABA generated 13C6-ring-labeled forms of 3-octaprenyl-4-aminobenzoic acid, 2-octaprenyl-aniline, and 3-octaprenyl-2-aminophenol, suggesting UbiA, UbiD, UbiX, and UbiI are capable of using pABA or pABA-derived intermediates as substrates. E. coli, S. cerevisiae, and human and mouse cells cultured in the presence of 13C6-resveratrol or 13C6-coumarate were able to synthesize 13C6-Q. Future evaluation of the physiological and pharmacological responses to dietary polyphenols should consider their metabolism to Q.